Diorganotin compounds containing α-aminoacidato schiff base ligands derived from functionalized 2-Hydroxy-5-(aryldiazenyl)benzaldehyde - Basu Baul, Tushar S.; Chaurasiya, Anurag; Rabha, Monosh; Khatua, Snehadrinarayan; Lyčka, Antonin; Schollmeyer, Dieter; Jurkschat, Klaus (Technische Universität Dortmund, 2020)
Three novel bicycloazastannoxides, namely, [nBu2Sn(L1)] (1), [nBu2Sn(L2)] (2) and [Bz2Sn(L3)] (3) were synthesized in one pot procedures by reacting diorganotin(IV) precursors with a mixture composed of an α-amino acid with either (E)-2-hydroxy-5-((4-nitrophenyl)diazenyl)benzaldehyde or (E)-2-hydroxy-5-(phenyldiazenyl)benzaldehyde. Single-crystal X-ray diffraction analysis reveal that compound 1 is monomeric, compound 2 consists of both a monomer and a dimer, while compound 3 is a coordination polymer for which two modifications 3A and 3B were identified. The 119Sn NMR chemical shifts measured in CDCl3 solutions indicate five-coordinate tin atoms for 1–3. Further, compounds 1 and 2 were found to be highly selective for sensing hydrogen sulfide in UV/Vis channel in CH3CN/H2O (9:1) media. The development of orange red color is likely the results of a Brønsted-type acid-base reaction of H2S with compounds 1 and 2, respectively, giving di-n-butyltin sulfide and the corresponding pro-ligands H2L1 and H2L2, respectively. Theoretical calculations accompany the experimental work.
syntheses, structures and sensing of hydrogen sulfide
European journal of inorganic chemistry;Vol. 2020, Issue18, pp 1803-1813
Keywords: Tin; Ligands with azo-imino groups; Structure elucidation; Sensing studies; 540